Crosslinking effect of dialdehyde cholesterol modified starch nanoparticles on collagen hydrogel. (1st June 2022) - Xu, Zhilang; Yuan, Lun; Liu, Qisong; Li, Defu; Mu, Changdao; Zhao, Lei; Li, Xinying; Ge, Liming
Abstract: Crosslinking is frequently used to improve the inherent poor physicochemical properties of collagen. However, local flocculation and irregular crosslinking of collagen would be unavoidably occurred once contacting with crosslinking agents due to widespread complex interactions. Herein, dialdehyde starch-based nanoparticles were developed to crosslink collagen as a new strategy. Starch was conjugated with cholesterol chloroformate before periodate oxidation to obtain dialdehyde cholesterol modified starch (DACS). DACS self-assembled into nanoparticles (DACSNPs) and crosslinked with collagen to fabricate collagen hydrogels (DACSNPs-Col). DACSNPs-Col hydrogels exhibited faster gelation rate, better uniform porous structure, higher mechanical properties and better degradation stability than dialdehyde starch crosslinked hydrogels. Significantly, DACSNPs-Col hydrogels show homogeneous structure, improved mechanical properties, low cytotoxicity, well blood compatibility, high cell adhesion and proliferation. Overall, the oxidized polysaccharide nanoparticles crosslinked collagen hydrogels have homogeneous and compact microstructure and improved physicochemical properties, which show potential application prospect in the field of tissue engineering scaffold. Graphical abstract: Unlabelled Image